The Posterior Cranial Vertical Line: A Novel Radiographic Marker for Classifying Global Sagittal Alignment - Park, Paul J.; Hassan, Fthimnir M.; Ferrer, Xavier E.; Morrissette, Cole; Lee, Nathan J.; Cerpa, Meghan; Sardar, Zeeshan M.; Kelly, Michael P.; Bourret, Stephane; Hasegawa, Kazuhiro; Wong, Hee-Kit; Liu, Gabriel; et al. (Neurospine, 2023)
Objective: To define a novel radiographic measurement, the posterior cranial vertical line (PCVL), in an asymptomatic adult population to better understand global sagittal alignment.Methods: We performed a multicenter retrospective review of prospectively collected radiographic data on asymptomatic volunteers aged 20–79. The PCVL is a vertical plumb line drawn from the posterior-most aspect of the occiput. The horizontal distances of the PCVL to the thoracic apex (TA), posterior sagittal vertical line (PSVL, posterosuperior endplate of S1), femoral head center, and tibial plafond were measured. Classification was either grade 1 (PCVL posterior to TA and PSVL), grade 2 (PCVL anterior to TA and posterior to PSVL), or grade 3 (PCVL anterior to TA and PSVL).Results: Three hundred thirty-four asymptomatic patients were evaluated with a mean age of 41 years. Eighty-three percent of subjects were PCVL grade 1, 15% were grade 2, and 3% were grade 3. Increasing PCVL grade was associated with increased age (p < 0.001), C7–S1 sagittal vertical axis (SVA) (p < 0.001), C2–7 SVA (p < 0.001). Additionally, it was associated with decreased SS (p = 0.045), increased PT (p < 0.001), and increased knee flexion (p < 0.001).Conclusion: The PCVL is a radiographic marker of global sagittal alignment that is simple to implement and interpret. Increasing PCVL grade was significantly associated with expected changes and compensatory mechanisms in the aging population. Most importantly, it incorporates cervical alignment parameters such as C2–7 SVA. The PCVL defines global sagittal alignment in adult volunteers and naturally distributes into 3 grades, with only 3% being grade 3 where the PCVL lies anterior to the TA and PSVL.